Comparison of the Outcomes of Open Haemorrhoidectomy Versus Procedure for Prolapse and Haemorrhoids (PPH) in the Treatment of Grades III and IV Haemorrhoids - Zafarullah, Hafiz Muhammad; Khan, Muhammad Ishaq; Faheem, Muhammad; Manzoor, Azhar (Biological and Clinical Sciences Research Journal, 2025)
Haemorrhoidal disease is common in Pakistan, with grades III and IV often requiring surgical intervention. While open haemorrhoidectomy has long been the standard, PPH is gaining popularity due to its minimally invasive nature. This study compares outcomes between these two surgical techniques. Objective: To compare operative time, intraoperative blood loss, postoperative pain, and healing time between open haemorrhoidectomy and PPH in patients with grade III and IV haemorrhoids. Methods: A randomized controlled trial was conducted at the Department of Surgery, Bahawal Victoria Hospital, Bahawalpur, from 16 January 2025 to 16 April 2025. Sixty patients with grade III or IV haemorrhoids were randomly assigned to undergo either PPH (Group A, n=30) or open haemorrhoidectomy (Group B, n=30). Outcomes were assessed using intraoperative and postoperative measures, including operative time, blood loss, pain (VAS), and wound healing. Data were analyzed using SPSS v25, with p ≤ 0.05 considered significant. Results: The mean operative time was significantly lower in the PPH group (15.1 ± 4.2 min) than in the open group (28.4 ± 5.9 min; p<0.001). Blood loss was also lower in the PPH group (76.3 ± 20.8 ml vs. 97.6 ± 31.1 ml; p<0.001). Postoperative pain scores were reduced (VAS: 2.9 ± 1.1 vs. 6.3 ± 1.4; p<0.001), and healing was faster (8.1 ± 2.4 vs. 14.8 ± 4.7 days; p<0.001). Stratified analysis showed these benefits were consistent across gender, BMI, and comorbidities. Conclusion: PPH provides superior outcomes compared to open haemorrhoidectomy in terms of operative efficiency and postoperative recovery. It is a safe and effective alternative for the surgical management of advanced haemorrhoids in the Pakistani population.